EVALUATION OF TOURISM COMPETITIVENESS AND ITS EFFECTS ON DESTINATION MANAGEMENT: MAKING A DIFFERENCE IN COSTA RICA? - Croes, Robertico (2013)
This study investigates whether the focus on inputs as measurement of tourism competitiveness provides a comprehensive understanding of the competitive position of a destination. Specifically the investigation is applied to Costa Rica in the context of the Central American region aiming at evaluating the impact of tourism competitiveness. The study applied descriptive and inductive statistics for an evaluation impact. This study found that the inputs focus is inconsistent with competitiveness as measured on the performance of a destination aiming at enhancing the quality of life. This inconsistency could confound a rational process of decisionmaking at the destination level. Two relevant algorithms are suggested to streamline a rational process relevant for destination managers in Costa Rica.